Post-2014 Afghanistan: Future scenarios from structure and agency perspectives - Wolf, Siegfried O. (Journal of South Asian Development, 2013)
This article aims to outline some potential developments in Afghanistan after the withdrawal of most of the foreign combat troops in 2014 from an agential as well as a structural perspective. To be able to do so, it is necessary to evaluate the performance of the international community in general and NATO’s International Security Assistance Force (ISAF) mission in particular over the last 11 years in Afghanistan as well as the role of the Afghan government under the leadership of President Hamid Karzai. In this context, the article will pay special attention to the most crucial question: how much peace is possible and how will the interlinked puzzle of the state, democracy and its institutions manifest itself? Finally the article shares some thoughts on future scenarios for Afghanistan. Based on the current, rather pessimistic, outlook, it will be argued that major armed conflicts will determine the political landscape.
Gesehen am 22.07.2021